STABILITY OF WHEAT GENOTYPES ADAPTED IN TROPICAL MEDIUM AND LOWLAND - Ashari, Sumeru; Waluyo, Budi; Yulianah, Izmi; Kendarini, Niken; Jusuf, Mohammad (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2012)
The research objective was to select wheat genotypes that can adapt on the medium and low plains. Twenty-seven genotypes and three varieties of wheat were grown in four locations in the medium and low plains since June-October 2009. The experiments were arranged using a randomized complete block design repeated three times. Analysis of variance performed at each location followed by a test of homogeneity of error range, the combined analysis of variance and yields stability analysis. Genotype x environment interaction significantly affecting yield. Stable genotypes and widely adaptable across locations were G-1 (1.94 t.ha-1), G-20 (1.24 t.ha-1), H-14 (1.85 t.ha-1), H-19 (1.59 t.ha-1), H-20 (1.69 t.ha-1), H-21 (1.48 t.ha-1), 162 (1.62 t.ha-1), 80 (1.63 t.ha-1), 82 (1.78 t.ha-1), 91 (1.49 t.ha-1), and 142 (1.45 t.ha-1). Genotypes adapted in productive environment were G-18 (1.23 t.ha-1), G-19 (1.63 t.ha-1), 185 (1.30 t.ha-1), 40 (1.33 t.ha-1) and 42 (1.52 t.ha-1). Genotypes adapted in marginal environments were 28 (2,22 t.ha-1), H-1 (1.61 t.ha-1), H-8 (1.65 t.ha-1) and H-16 (1.68 t.ha-1). Genotype was selected as an improvement material in the wheat breeding in medium and lowland of tropical regions. Â Keywords: wheat selection, tropical, yield stability and adaptability